2020
DOI: 10.3390/ijgi9110619
|View full text |Cite
|
Sign up to set email alerts
|

LionVu 2.0 Usability Assessment for Pennsylvania, United States

Abstract: The Penn State Cancer Initiative implemented LionVu 1.0 (Penn State University, United States) in 2017 as a web-based mapping tool to educate and inform public health professionals about the cancer burden in Pennsylvania and 28 counties in central Pennsylvania, locally known as the catchment area. The purpose of its improvement, LionVu 2.0, was to assist investigators answer person–place–time questions related to cancer and its risk factors by examining several data variables simultaneously. The primary object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Since ArcGIS Online is proprietary, we found that moving to a HIPAA-protected server a payment is necessary, and it was challenging to add newer data to the tool. In response, LionVu was redesigned using Leaflet JavaScript, and a usability assessment was completed [ 12 ]. Leaflet uses the Web Mercator projection, which is based on WGS84 and remains the de facto projection for web mapping applications [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since ArcGIS Online is proprietary, we found that moving to a HIPAA-protected server a payment is necessary, and it was challenging to add newer data to the tool. In response, LionVu was redesigned using Leaflet JavaScript, and a usability assessment was completed [ 12 ]. Leaflet uses the Web Mercator projection, which is based on WGS84 and remains the de facto projection for web mapping applications [ 13 ].…”
Section: Introductionmentioning
confidence: 99%